2010
DOI: 10.1371/journal.pone.0012367
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Naturally Occurring Tumor Immunity: A Clinical Vaccine Trial in Prostate Cancer

Abstract: BackgroundStudies of patients with paraneoplastic neurologic disorders (PND) have revealed that apoptotic tumor serves as a potential potent trigger for the initiation of naturally occurring tumor immunity. The purpose of this study was to assess the feasibility, safety, and immunogenicity of an apoptotic tumor-autologous dendritic cell (DC) vaccine.Methods and FindingsWe have modeled PND tumor immunity in a clinical trial in which apoptotic allogeneic prostate tumor cells were used to generate an apoptotic tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…25,3337 However, the clinical responses to some of these vaccines in patients with metastatic disease have not always been successful, 38 likely reflecting the fact that vaccines are often administered to patients with bulky or metastatic disease whose immune systems are frequently compromised because of disease burden and prior therapy and whose tumors express or overexpress ‘self antigens’ that are poorly immunogenic and against which circulating T cells are often anergized or tolerized. 39 …”
Section: Discussionmentioning
confidence: 99%
“…25,3337 However, the clinical responses to some of these vaccines in patients with metastatic disease have not always been successful, 38 likely reflecting the fact that vaccines are often administered to patients with bulky or metastatic disease whose immune systems are frequently compromised because of disease burden and prior therapy and whose tumors express or overexpress ‘self antigens’ that are poorly immunogenic and against which circulating T cells are often anergized or tolerized. 39 …”
Section: Discussionmentioning
confidence: 99%
“…Interaction with apoptotic cells not always suppresses immunity. Phagocytosis of stressed, activated, tumor, or infected cells undergoing apoptosis promotes DC maturation and immunity, and proinflammatory apoptotic cells have been tested to boost immunity for vaccination against cancer and pathogens . Besides the intrinsic properties of the apoptotic cells, the rate of apoptotic cell clearance, the microenvironment where it occurs, and the opsonins deposited on the apoptotic cells are factors that influence the impact of apoptotic cells on the target APCs and therefore, the consequent ability of the APCs to stimulate or suppress immunity .…”
Section: Introductionmentioning
confidence: 99%
“…Cloning of the cerebellar antigen (cdr2) associated more commonly with gynecologic cancer revealed the presence of antigen-specific T cells in these patients, establishing a cellmediated component to the disorders, as well as a means by which tumor antigen is likely cross-presented from apoptotic cells to dendritic cells to initiate the anti-tumor immune response (12,13). These studies have led to clinical cancer vaccine trials in prostate cancer patients that have shown some evidence of efficacy in Phase I safety studies (14). Moreover, cloning of the genes encoding T cell receptors from these patients offers a possible new therapeutic strategy, by passive transfer of these genes into T cells to induce tumor-cell targeting (15).…”
mentioning
confidence: 99%